2018
DOI: 10.1002/hep4.1269
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Triggering Receptor Expressed on Myeloid Cells 1 Ameliorates Inflammation and Macrophage and Neutrophil Activation in Alcoholic Liver Disease in Mice

Abstract: Alcoholic liver disease (ALD) is characterized by macrophage and neutrophil leukocyte recruitment and activation in the liver. Damage‐ and pathogen‐associated molecular patterns contribute to a self‐perpetuating proinflammatory state in ALD. Triggering receptor expressed on myeloid cells 1 (TREM‐1) is a surface receptor that amplifies inflammation induced by toll‐like receptors (TLRs) and is expressed on neutrophils and monocytes/macrophages. We hypothesized that TREM‐1 signaling contributes to proinflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 45 publications
2
16
0
Order By: Relevance
“…However, dysbiosis and translocation of gut bacteria and bacterial products due to intestinal barrier dysfunction result in the excessive presence of PAMPs within the hepatic microvasculature that reach the liver via the portal vein (195) which, in murine models, drives inflammasome activation of profibrotic hepatic stellate cells (196, 197). In a recent publication the cell-specific innate immune receptor triggering receptor expressed on myeloid cells-1 (TREM-1) was reported to promote hepatic inflammation and fibrosis in mice and humans (198), and inhibition of TREM-1 in mice ameliorated inflammation and macrophage and neutrophil activation in a mouse model of ARLD (199).…”
Section: Neutrophil Mediated Liver Injurymentioning
confidence: 99%
“…However, dysbiosis and translocation of gut bacteria and bacterial products due to intestinal barrier dysfunction result in the excessive presence of PAMPs within the hepatic microvasculature that reach the liver via the portal vein (195) which, in murine models, drives inflammasome activation of profibrotic hepatic stellate cells (196, 197). In a recent publication the cell-specific innate immune receptor triggering receptor expressed on myeloid cells-1 (TREM-1) was reported to promote hepatic inflammation and fibrosis in mice and humans (198), and inhibition of TREM-1 in mice ameliorated inflammation and macrophage and neutrophil activation in a mouse model of ARLD (199).…”
Section: Neutrophil Mediated Liver Injurymentioning
confidence: 99%
“…In this study, we observed that mice treated with morin hydrate showed decreased levels of pro-inflammatory cytokines in lungs during influenza infection, which may be associated with its effects on immune cells, in addition to direct inhibition of influenza virus entry. It reduced the expression of LPS-induced TNF-α and IL-1β in RAW264.7 macrophage cell line ( 10 ) and also inhibited TREM-1, which is highly expressed receptor in neutrophils, monocytes and macrophages ( 38 39 40 ). However, further studies are needed to understand whether the anti-viral effects of morin hydrate are mediated through modulation of immune cell activation, or solely through the inhibition of influenza virus entry.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study suggested that TREM-1 receptor also mediated in reversing M2 polarization induced by hypoxia (18). Although the specific ligands of TREM-1 have not been identified yet, it has been revealed that TREM-1 activation amplifies the TLR2/4-mediated proinflammatory signals, allowing the secretion of proinflammatory chemokines and cytokine (14,17). Moreover, recent studies have demonstrated that TREM-1 mediated signaling modulation of M1 macrophage activation promoted the inflammatory response in alcoholic liver disease and obesity-induced fatty liver disease (18,20).…”
Section: Discussionmentioning
confidence: 99%
“…Upon activation, TREM-1 can trigger and augment inflammatory reaction, especially through synergism with toll-like receptors (TLRs) signaling in macrophages (13)(14)(15)(16). Moreover, several studies have already revealed that TREM-1 play an important role in regulating the activation of Kupffer cell and is associated with macrophages polarization, which amplifies acute and chronic inflammatory responses in diseases (17)(18)(19). Interestingly, a recent report has demonstrated that overexpression of TREM-1 in the liver and M1 hepatic macrophages polarization were associated with obesity-induced insulin resistance (IR) (20).…”
Section: Introductionmentioning
confidence: 99%